2017
DOI: 10.1109/tnsre.2017.2687100
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Fall-Risk Prediction Models for Older Adults Based on Wearable Sensors

Abstract: Wearable sensors can provide quantitative, gait-based assessments that can translate to point-of-care environments. This investigation generated elderly fall-risk predictive models based on wearable-sensor-derived gait data and prospective fall occurrence, and identified the optimal sensor type, location, and combination for single and dual-task walking. 75 individuals who reported six month prospective fall occurrence (75.2 ± 6.6 years; 47 non-fallers and 28 fallers) walked 7.62 m under single-task and dual-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
81
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(109 citation statements)
references
References 37 publications
7
81
1
5
Order By: Relevance
“…The types of populations (retrospective or prospective fallers; single-fall or multiple-fall fallers) and methodologies vary, and differ from the current paper. The prospective fall prediction study in [26] permits comparison based on the identical older-adult population. The turn-feature based classification results in this paper (73.4% accuracy, 60.5% sensitivity, 82.0% specificity, and 0.44 MCC score) were better than the best straight-walking classification results in [26] (56.5% accuracy, 42.5% sensitivity, 65.4% specificity and 0.083 MCC score), based on similar accelerometer derived features for 25 ft walk single-task and dual-task tests, and similar cross validation with 10,000 random stratified splits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The types of populations (retrospective or prospective fallers; single-fall or multiple-fall fallers) and methodologies vary, and differ from the current paper. The prospective fall prediction study in [26] permits comparison based on the identical older-adult population. The turn-feature based classification results in this paper (73.4% accuracy, 60.5% sensitivity, 82.0% specificity, and 0.44 MCC score) were better than the best straight-walking classification results in [26] (56.5% accuracy, 42.5% sensitivity, 65.4% specificity and 0.083 MCC score), based on similar accelerometer derived features for 25 ft walk single-task and dual-task tests, and similar cross validation with 10,000 random stratified splits.…”
Section: Discussionmentioning
confidence: 99%
“…The prospective fall prediction study in [26] permits comparison based on the identical older-adult population. The turn-feature based classification results in this paper (73.4% accuracy, 60.5% sensitivity, 82.0% specificity, and 0.44 MCC score) were better than the best straight-walking classification results in [26] (56.5% accuracy, 42.5% sensitivity, 65.4% specificity and 0.083 MCC score), based on similar accelerometer derived features for 25 ft walk single-task and dual-task tests, and similar cross validation with 10,000 random stratified splits. Those results for straight walking were similar to the straight-walking-based classification results in Test II of this paper (55.5% accuracy, 46.1% sensitivity, 61.8% specificity and 0.08 MCC).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [21], three feature selection algorithms were examined, i.e., Relief, Simba, and mRMR, and it was reported that these algorithms yielded similar feature importance, especially for the first four highest ranked features. Relief-F [47], which is an extended version of Relief [48], was reported as the best feature selection algorithm in [49] compared to Fast Correlation Based Filter and Correlation Based Feature Selection. It was one of the most widely used feature selection algorithms, with low computational time [50] and the ability to deal with incomplete and noisy data, and can be used for evaluating feature quality in multi-class problems [51].…”
Section: Discussionmentioning
confidence: 99%